2021
DOI: 10.1109/mcg.2021.3116042
|View full text |Cite
|
Sign up to set email alerts
|

Remote Instruction for Data Visualization Design—A Report From the Trenches

Abstract: In this paper, we report on our experiences of running visual design workshops within the context of a Master's level data visualization course, in a remote setting. These workshops aim to teach students to explore visual design space for data by creating and discussing hand-drawn sketches. We describe the technical setup employed, the different parts of the workshop, how the actual sessions were run, and to what extent the remote version can substitute for in-person sessions. In general, the visual designs cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…They describe activities that engage students in the use of visualization guidelines to support teaching, learning, and discussion around visualization guidelines using the online VisGuides forum [DAREA * 18]. Schwab et al developed a tool to use for online synchronous collaboration [SSB * 21], and Aerts et al [APB * 21] reported on their experience of running online design workshops for a master's‐level visualization course where students were taught to ideate, create, and discuss hand‐drawn sketches. However, the concept of teaching and implementing the whole design study process in an online visualization class is not yet explored.…”
Section: Related Workmentioning
confidence: 99%
“…They describe activities that engage students in the use of visualization guidelines to support teaching, learning, and discussion around visualization guidelines using the online VisGuides forum [DAREA * 18]. Schwab et al developed a tool to use for online synchronous collaboration [SSB * 21], and Aerts et al [APB * 21] reported on their experience of running online design workshops for a master's‐level visualization course where students were taught to ideate, create, and discuss hand‐drawn sketches. However, the concept of teaching and implementing the whole design study process in an online visualization class is not yet explored.…”
Section: Related Workmentioning
confidence: 99%